2013
DOI: 10.1089/cyber.2012.0254
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Group Membership on Collaborative Learning with Wikis

Abstract: The social web stimulates learning through collaboration. However, information in the social web is often associated with information about its author. Based on previous evidence that ingroup information is preferred to outgroup information, the current research investigates whether group memberships of wiki authors affect learning. In an experimental study, we manipulated the group memberships (ingroup vs. outgroup) of wiki authors by using nicknames. The designated group memberships (being fans of a soccer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…If rules and roles are important for individual learning, but remain unclear in a given situation, then people are bound to look for other indications of social preferences. Indeed, based on self-categorization theory (Turner, 1987), a study by Matschke, Moskaliuk, and Kimmerle (2013) identified people's group membership (see Tanis & Postmes, 2003) as a moderator that has an impact on individual learning in social contexts. This experiment showed that users integrated information into their cognitive systems to a different extent depending on whether the information originated from members of the in-group or from the out-group.…”
Section: Triggers and Moderators Of Internalizationmentioning
confidence: 99%
“…If rules and roles are important for individual learning, but remain unclear in a given situation, then people are bound to look for other indications of social preferences. Indeed, based on self-categorization theory (Turner, 1987), a study by Matschke, Moskaliuk, and Kimmerle (2013) identified people's group membership (see Tanis & Postmes, 2003) as a moderator that has an impact on individual learning in social contexts. This experiment showed that users integrated information into their cognitive systems to a different extent depending on whether the information originated from members of the in-group or from the out-group.…”
Section: Triggers and Moderators Of Internalizationmentioning
confidence: 99%
“…In this vein, we included group membership, in‐group size, out‐group size, leader's and aid workers' age and gender, and armed conflict setting. Previous organizational studies, including recent ones by Matschke, Moskaliuk, and Kimmerle () and Horwitz and Horwitz (), suggest a relationship between group membership and employees' learning performance. These insights highlight that group membership affects how people share, assess, and integrate information across groups.…”
Section: Methodsmentioning
confidence: 90%
“…Wikipedia is one of the collaborative knowledge structures, which is a kind of group knowledge structure formed through independent work, discussions between the individuals and collaborative cognition process based on common understanding of cognitive object [27]. The social web stimulates learning through collaboration, in addition, individuals apply social selection strategies when considering information from Wikipedia [22]. After investigating the ways that participation in the Wikipedia community, Bryant et al [4] found that as individuals' participation becomes more central and frequent, their motivation seems to transform from a local focus on individual articles to become rooted in a concern for the quality of the Wikipedia content as a whole and the health of the community.…”
Section: Concept Frameworkmentioning
confidence: 99%